Faktor-Faktor yang Berhubungan dengan Kejadian Gagal Ginjal Kronik di RSUD dr. Djasamen Saragih Pematangsiantar Tahun 2025 - Situngkir, Grace Silva Sabatini; ., Jemadi (Jurnal Penelitian Kesmasy, 2025)
Chronic Kidney Failure (CKF) is a condition in which the kidneys are damaged so that they cannot function normally. In 2024, chronic kidney disease is included in the 10 causes of death in the world. This study aims to determine the factors related with the incidence of chronic kidney disease at dr.Djasamen Saragih Regional General Hospital Pematangsiantar in 2025. This study is a quantitative study with a cross-sectional design. The sample size was 96 respondents with a purposive sampling technique and analyzed with the chi-square test (α=0.05). The results of the study showed that the proportion of chronic kidney disease was (58.3%) and the highest proportion distribution was at the age of 18-59 years (62.5%), female (57.3%), had a high level of education (68.8%), had a working status (61.5%), had hypertension ≤5 years (40.63), no history of diabetes mellitus (58.3%), no history of kidney stones (87.5%), consumed <8 glasses of water per day (70.8%), and didn’t consume instant packaged drinks (59.4%). There was a significant relationship between employment status (p=0.006), hypertension (p=0.029), diabetes mellitus (p=0.043), consumption of water (p=0.0001), and consumption of instant packaged drinks (p=0.003) with the incidence of chronic kidney failure. Meanwhile, there was no significant relationship between age (p=1.000), gender (p=0.197), education level (p=0.118), and history of kidney stones (p=0.060) with the incidence of chronic kidney failure. It is expected that the community reducing consumption of packaged drinks and consuming enough water and routinely controlling the disease they suffer from to prevent complications.